The Blackthorn key - Sands, Kevin (Aladdin, 2016)
In 1665 London, fourteen-year-old Christopher Rowe, apprentice to an apothecary, and his best friend, Tom, try to uncover the truth behind a mysterious cult, following a trail of puzzles, codes, pranks, and danger toward an unearthly secret with the power to tear the world apart.